2021
DOI: 10.1088/1742-6596/1898/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Usability Testing for Student Academic Information System in State Polytechnic of Creative Media

Abstract: SIAM (Student Academic Information System) is an academic services information system that has been implemented at the State Polytechnic of Creative Media (Polimedia). It’s been two months SIAM has been integrated using Single Sign On (SSO). After we implemented SIAM new version we received a lot of complaints every day. In this research, the authors conducted a usability test on the SIAM new version in order to determine the effectiveness and performance of the application. Usability test components include e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…), Sukmasetya et al (2020), Al-Kinani et al (2020), Alturki et al (2020), Al-Gayar et al (2021), A'bas et al (2021) where they found that applications were easy to learn.The native G-MoMo applications were effective for mobile money subscribers because they could complete their tasks accurately. This is in line with the works ofByun et al (2020),Hussain et al (2020),Alturki et al (2020),Tyas and Khairunisa (2020),Emanuela et al (2020),Mubeen et al (2020),Lowe et al (2021Lowe et al ( ), A'bas et al (2021, who reported that there was effectiveness with the applications.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…), Sukmasetya et al (2020), Al-Kinani et al (2020), Alturki et al (2020), Al-Gayar et al (2021), A'bas et al (2021) where they found that applications were easy to learn.The native G-MoMo applications were effective for mobile money subscribers because they could complete their tasks accurately. This is in line with the works ofByun et al (2020),Hussain et al (2020),Alturki et al (2020),Tyas and Khairunisa (2020),Emanuela et al (2020),Mubeen et al (2020),Lowe et al (2021Lowe et al ( ), A'bas et al (2021, who reported that there was effectiveness with the applications.…”
supporting
confidence: 86%
“…( It was reported that the usability testing result showed that the native G-MoMo applications were highly efficient because mobile money subscribers could take less time to complete the given tasks accurately (Lynn et al, 2020;Byun et al, 2020;Hussain et al, 2020;Zakaria et al, 2020;Sukmasetya et al, 2020;Tyas & Khairunisa, 2020;Emanuela et al, 2020;Mubeen et al, 2020;A'bas et al, 2021;Putri et al, 2021).…”
Section: Heuristic Evaluation and Usability Testingmentioning
confidence: 99%
“…Abidin et al (2019) recommended that applications must have help and documentation features explained in simple language and easily accessible. It was reported that the usability testing result showed that the native G-MoMo applications were highly efficient because mobile money subscribers could take less time to complete the given tasks accurately (Lynn et al, 2020;Byun et al, 2020;Hussain et al, 2020;Zakaria et al, 2020;Sukmasetya et al, 2020;Tyas & Khairunisa, 2020;Emanuela et al, 2020;Mubeen et al, 2020;A'bas et al, 2021;Putri et al, 2021).…”
Section: Heuristic Evaluation and Usability Testing (I) Several Usabi...mentioning
confidence: 99%
“…,Zakaria et al (2020),Alturki et al (2020),Tyas and Khairunisa (2020),Emanuela et al (2020),Mubeen et al (2020),), Al-Gayar et al (2021,Putri et al (2021),Lowe et al (2021), andA'bas et al (2021), where it was found that the users were satisfied with the applications.…”
mentioning
confidence: 99%
“…,Zakaria et al (2020),Alturki et al (2020),Tyas and Khairunisa (2020),Emanuela et al (2020),Mubeen et al (2020),), Al-Gayar et al (2021,Putri et al (2021),Lowe et al (2021), andA'bas et al (2021), where it was found that the users were satisfied with the applications.…”
mentioning
confidence: 99%